PENGEMBANGAN MEDIA PEMBELAJARAN MINIATUR MUATAN IPAS MATERI SIKLUS AIR KELAS V SD - Lafega Khoirunisa Az-Zahra; Nabila Aulia Putri; Anggi Citra Apriliana; Taofik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The lack of student interest in reading, along with the limitations of educational media, has resulted in students falling behind academically, particularly in the material of water cycles, as the teacher does not use educational media and students have less additional knowledge in learning the material. The purpose of this study is to develop Miniature Educational Media for IPAS Water Cycle Material. The type of research used in this study is Research and Development (R & D). The instruments used in this study are questionnaires. The questionnaire includes three types according to the role and position of the respondents in this study, namely: (1) media expert questionnaire, (2) language expert questionnaire, (3) material expert questionnaire, and (4) respondent questionnaire. The subjects of this study are media experts, material experts, and language experts who are lecturers from the Elementary Education Department, Faculty of Education, University of Jakarta. Additionally, there are 30 fifth-grade students from SDN Mekarjaya 14. The results of the study show that the validation of the media expert test obtained a result of 98.75%, the validation of the language expert test 92%, the validation of the material expert test 80%, and the total overall result 93.58%. Based on the results of the questionnaire recapitulation, the evaluation score was 93.33% at the one-to-one evaluation stage, 87.42% at the small group evaluation stage, and 88.66% at the field test evaluation stage.